SISTEM PEMERINTAHAN ONDERAFDEELING OGAN ILIR TAHUN 1906-1942 - Aldi; Egy Gusti Hawali; MHD Irwan; Syarifuddin; Supriyanto (Universitas Sultan Ageng Tirtayasa, 2021)
During the Dutch Colonial Government, the South Sumatra region was part of the Palembang Residency divided into several administrative areas ranging from afdeeling to hamlets. At first Onderafdeeling Ogan Ilir was one of the afdeeling areas in the Residency of Palembang. However, since 1906 it changed its status to an onderafdeeling area. The status of Onderafdeeling Ogan Ilir just ended since the Dutch colonial government handed over its power to Japan in 1942. This study aims to find out how the system of government of Onderafdeeling Ogan Ilir was in 1906-1942. This study used the historical method with four stages of research, namely heuristics, criticism, interpretation, and historiography. The results of the study found that Onderafdeeling Ogan Ilir used the Dutch Colonial Government System consisted of a system of government onderafdeeling (controleur), marga (pasirah), hamlet (kerio) and also had a People's Council known as Onderafdeeling Raad Ogan Ilir.